Metastable structures and size effects in small group dynamics - Lauro Grotto, Rosapia; Guazzini, Andrea; Bagnoli, Franco (Frontiers in Psychology, 2014)
In his seminal works on group dynamics Bion defined a specific therapeutic setting allowing psychoanalytic observations on group phenomena. In describing the setting he proposed that the group was where his voice arrived. This physical limit was later made operative by assuming that the natural dimension of a therapeutic group is around 12 people. Bion introduced a theory of the group aspects of the mind in which proto-mental individual states spontaneously evolve into shared psychological states that are characterized by a series of features: 1) they emerge as a consequence of the natural tendency of (both conscious and unconscious) emotions to combine into structured group patterns; 2) they have a certain degree of stability in time; 3) they tend to alternate so that the dissolution of one is rapidly followed by the emergence of another; 4) they can be described in qualitative terms according to the nature of the emotional mix that dominates the state, in structural terms by a kind of typical 'leadership’ pattern, and in 'cognitive’ terms by a set of implicit expectations that are helpful in explaining the group behavior (i.e. the group behaves 'as if’ it was assuming that…). Here we adopt a formal approach derived from Socio-physics in order to explore some of the structural and dynamic properties of this small group dynamics. We will described data from an analytic DS model simulating small group interactions of agents endowed with a very simplified emotional and cognitive dynamic in order to assess the following main points: 1) are metastable collective states allowed to emerge in the model and if so, under which conditions in the parameter space? 3) can these states be differentiated in structural terms? 3) to what extent are the emergent dynamic features of the systems dependent of the system size? We will finally discuss possible future applications of the quantitative descriptions of the interaction structure in the small group clinical setting.